Presenting a Model of Factors Influencing Business Competitiveness in the Petrochemical Industry - Hatami, Abolghasem; Hassni, Seyyed Reza; Namamian, Farshid; Kahrizi, Omid Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Competitiveness at the organizational level is a concept that numerous theories have addressed, each proposed by different researchers from diverse perspectives. In a market-based economy, firms compete with each other to attract more customers, continually monitoring each other’s behaviors and adopting various strategies to achieve success. Consequently, competition drives firms to perform optimally, produce high-quality goods, and provide services at the lowest possible cost. This study aims to examine and identify the components of a competitiveness model in the petrochemical industry and ultimately design and present a relevant model to foster growth in this sector. Methodology: By using an integrated approach to implement the DEMATEL and ISM methods for constructing the reachability matrix instead of using the SSIM matrix, the outputs of the DEMATEL method (T matrix) were relied upon. Findings: For forming the reachability matrix, values smaller than the threshold in the T matrix were considered insignificant relationships (equivalent to zero), and values larger than the threshold (significant relationships) were considered equivalent to one. Based on the results obtained from implementing the ISM method, the model of interrelationships among the components was depicted. Conclusion: The resulting model illustrates the significant relationships of elements at each level to elements at the subsequent level, as well as significant relationships among elements within each row. Additionally, this model considers the meaningful reciprocal and feedback relationships obtained from the DEMATEL method.